Dapagliflozin ameliorates kidney injury following limb ischemia-reperfusion via the AMPK/SIRT1/NLRP3 pathway - Qiuxiao Zhu; Huiyao Hao; Ya Gao; Na Li; Zibo Liu; Linyi Shu; Qian Wang; Lihui Zhang (Renal Failure)
Limb ischemia-reperfusion (I/R) results in both localized tissue harm and injury to distant organs, particularly affecting the kidneys and leading to acute kidney injury. This study evaluates the renoprotective effect of dapagliflozin, a drug frequently prescribed for type 2 diabetes management, in relation to kidney injury caused by limb I/R. The extent of kidney injury was detected through serum marker testing in the rat model. Oxidative stress indicators and inflammatory factors were evaluated in rat and cellular models. Histological changes in the kidneys were examined using HE staining and electron microscopy. Cell pyroptosis was quantified using both TUNEL staining and flow cytometry. Cellular mitochondrial function was analyzed with JC-1 staining. AMPK/SIRT1/NLRP3 pathway-related proteins and their mRNAs were assessed via western blotting and RT-qPCR techniques. We showed that dapagliflozin reduced serum CRE, BUN, NGAL and KIM-1 levels and improved renal pathology in rat. Additionally, dapagliflozin significantly raised the concentrations of GSH-Px and SOD, concurrently reduced MDA and ROS levels in vivo and in vitro. It also lowered the levels of IL-6 and TNF-α and reduced cell pyroptosis. Furthermore, it was observed that dapagliflozin elevated AMPK and SIRT1 expressions, while decreasing NLRP3, ASC, GSDMD, IL-1β, and caspase-1 expressions. Notably, these effects of dapagliflozin were diminished in the presence of AMPK siRNA. Taken together, dapagliflozin exhibits a significant protective effect against kidney injury resulting from limb I/R. This protective effect operates through the inhibition of pyroptosis by activating the AMPK/SIRT1/NLRP3 signaling pathway.